Prevalence and Risk Factors of Congenital Disabilities in China, India, and Indonesia: A Systematic Review - Wulandari, M; Bantas, K (KnE Life Sciences, 2019)
Congenital disabilities are one causes of mortality to the neonatal and children under five around the world. Children with congenital disabilities who survive may have a mental, physical, visual or auditory handicapped in their lifetime. Congenital disabilities generally caused by several multifactorial causes which related each other. The purpose of this research to compare prevalence and types of risk factors of congenital disabilities which most frequently researched in China, India, and Indonesia. This research is a systematic review by analyzing the relevant research journals from 2012 – 2017, make an assumption and conclude these journals. The prevalence of congenital disabilities in China, India, and Indonesia is varied. The highest prevalence is in Pune city, India 230,51/10,000 birth. Based on the risk factors which frequently researched is mother factors: gestational age of mother ≥ 35 years old and poor maternal education; environmental factors: mother living in urban area and living in slum area; nutrition factor: folic acid deficiency; child factors : age of fetuses when first detected, low birth weight, prematurity and baby boy; and other factor : genetics. In Indonesia, the risk factors of the congenital disabilities studied are gestational age of mother and the environmental factors where a pregnant woman lives. Identifying risk factors is useful for making intervention programs to decrease the prevalence of congenital disabilities. Keywords: prevalence, risk factors, congenital disabilities, systematic review